Explaining Non-Employment Magnitude and Duration: The Case of Italy - Bruno Contini; Roberto Quaranta (Institute of Labor Economics (IZA), 2017)
In the past 25 years a vast number of Italian workers have become jobless for long periods of time, often dropping out of the labor market and becoming long-term inactives for the rest of their life. This process has long roots in the past and has been fuelled by Italy's poor economic performance. We intend to analyse its nature and derive policy implications for the years to come. We estimate long-term non-employment and its duration by means of Italian longitudinal databases of administrative origin. Long-term non-employment of men stands at 1.6 million individuals in 2012, about the size of male official unemployment, its average duration exceeding 14 years. We present a micro-econometric exploration of the underlying process. The main driving element works via a substitution effect: the relative cost of new entrants vs. that of retaining individuals already on-the-job has often been too high and widely responsible for such developments as it provides the employers with an incentive to layoff and fill the vacancy with a new entrant. Additional explanation is provided by the wide utilization of temporary and flexible contracts and by reasonable proxies of individual characteristics. Our conclusions indicate important drawbacks in the strategy advocated for many years by the EU Commission to promote youth employment.
Keywords: J08; J11; J64; J68; 330; inactivity; long run consequences of unemployment/non employment